Exploring Sustainable Finance: A Qualitative Inquiry into Responsible Investment and ESG Risk Evaluation - Yunus, Yana Ameliana; Nanda, Sahabuddin (Manunggal Halim Jaya, 2024)
This research explores the landscape of sustainable finance, responsible investment, and ESG (Environmental, Social, and Governance) risk evaluation, aiming to understand their complexities and implications for financial markets and sustainability outcomes. Employing a qualitative research approach, the study conducts a comprehensive review and synthesis of existing literature, drawing insights from academic databases, journals, reports, and other relevant sources. The research design involves purposive sampling of literature based on relevance, rigor, credibility, and significance criteria. Data collection comprises systematic review and analysis of scholarly literature, while thematic analysis is employed for data interpretation. The findings underscore the growing recognition of ESG factors' importance in investment decision-making processes, driven by their materiality to financial performance and sustainability outcomes. Institutional investors play a pivotal role in mainstream adoption of responsible investment practices, driven by the acknowledgment of ESG factors' impact on investment risk and return profiles. However, methodological challenges related to ESG data quality, measurement, and comparability persist, hindering effective ESG integration and risk assessment. Regulatory initiatives like the United Nations Principles for Responsible Investment (PRI) and the Task Force on Climate-related Financial Disclosures (TCFD) have contributed to mainstreaming ESG considerations but face challenges of regulatory fragmentation and inconsistencies. Addressing these challenges requires collaborative efforts from stakeholders to develop standardized ESG reporting frameworks, enhance stakeholder engagement, and promote regulatory coherence. This study contributes to understanding sustainable finance dynamics and calls for interdisciplinary collaboration to bridge financial theory, sustainability science, and regulatory policy.